2005
DOI: 10.1007/s00415-005-0725-z
|View full text |Cite
|
Sign up to set email alerts
|

Release of brain–type and heart–type fatty acid–binding proteins in serum after acute ischaemic stroke

Abstract: This study aimed at an analysis of the release of Braintype and Heart-type Fatty Acid- Binding Proteins (B-FABP and HFABP) in acute ischaemic stroke and their potential value as neurobiochemical markers of brain damage. We investigated 42 consecutive patients admitted within 6 hours after ischaemic stroke. Serial venous blood samples were taken hourly between 1 to 6 hours, and at 12, 18, 24, 48, 72, 96, and 120 hours after stroke onset. In all patients lesion topography was assessed and infarct volume was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 40 publications
3
42
0
1
Order By: Relevance
“…We also found that A-FABP is one of the most abundant proteins secreted from adipocytes and confirmed the presence of circulating A-FABP in humans. In line with our results, data from previous studies have shown that several members of the FABP family, including H-FABP (33 ), L-FABP (34 ), intestine-type FABP (I-FABP) (35 ), and brain-type FABP (B-FABP) (36 ), are present in the human bloodstream, presumably being released from the cells via direct diffusion. Recent data indicated that H-FABP is a promising plasma biomarker for early and sensitive diagnosis of acute coronary heart syndrome and myocardial infarction in heart failure (33 ) and that B-FABP may be a plasma biomarker for the detection of brain injury (36 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that A-FABP is one of the most abundant proteins secreted from adipocytes and confirmed the presence of circulating A-FABP in humans. In line with our results, data from previous studies have shown that several members of the FABP family, including H-FABP (33 ), L-FABP (34 ), intestine-type FABP (I-FABP) (35 ), and brain-type FABP (B-FABP) (36 ), are present in the human bloodstream, presumably being released from the cells via direct diffusion. Recent data indicated that H-FABP is a promising plasma biomarker for early and sensitive diagnosis of acute coronary heart syndrome and myocardial infarction in heart failure (33 ) and that B-FABP may be a plasma biomarker for the detection of brain injury (36 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, data from previous studies have shown that several members of the FABP family, including H-FABP (33 ), L-FABP (34 ), intestine-type FABP (I-FABP) (35 ), and brain-type FABP (B-FABP) (36 ), are present in the human bloodstream, presumably being released from the cells via direct diffusion. Recent data indicated that H-FABP is a promising plasma biomarker for early and sensitive diagnosis of acute coronary heart syndrome and myocardial infarction in heart failure (33 ) and that B-FABP may be a plasma biomarker for the detection of brain injury (36 ). Our immunoassay results for human A-FABP revealed that in lean persons the circulating concentration of this protein is substantially higher than those of several other major adipokines and/or cytokines secreted from adipose tissue, including resistin, leptin, tumor necrosis factor-␣, interleukin-6, and C-reactive protein (27,37,38 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results were recently reinforced by 3 independent studies, showing an increase of heart-type fatty acid-binding protein in patients suffering from mild traumatic brain injury (34 ), stroke (35 ), and neurodegenerative diseases with dementia (36 ). We believe the model of postmortem CSF may partly reproduce mechanisms underlying the ischemic cascade of events leading to stroke lesions and, as such, may confer scientific plausibility to the biomarkers identified.…”
Section: Discussionsupporting
confidence: 67%
“…Recently it was demonstrated that the serum level of B-FABP is a sensitive marker for brain injury. (28)(29)(30) B-FABP in the serum or urine as a potential diagnostic and prognostic marker for RCC is currently under investigation. Total 13 0 0 1 12 0 3 2 8 4 3 2 4 Nuclear grade G1 3 --1 2 -1 1 1 1 -1 1 G2 8 ---8 -2 1 5 2 3 1 2 G3 2 ---2 ---2 1 --1 T category pT1a 8 --1 7 -3 1 4 2 2 -4 pT1b 2 ---2 ---2 -1 1 -pT2 3 ---3 --1 2 2 -1 -Stage Stage I 10 --1 9 -3 1 6 2 3 1 4 Stage II 3 ---3 --1 2 2...…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification was performed for each gene using the indicated primers. The PCR protocol was at 95°C for 5 min followed by 30 2700 (Applied Biosystems, Tokyo, Japan). The PCR product was analyzed on 3% agarose, as described previously.…”
Section: Methodsmentioning
confidence: 99%